Testing X-Ray Reprocessing and Mapping the Soft Excess of NGC 7469 with NICER - Ethan R. Partington; Edward M. Cackett; Rick Edelson; Keith Horne; Jake A. Miller; Aaron J. Barth; Jonathan Gelbord; Juan V. Hernández Santisteban (The Astrophysical Journal)
We present an X-ray/UV reverberation analysis of NGC 7469 across 210 days, using daily NICER observations with contemporaneous monitoring by Swift UVOT+XRT. We model the X-ray spectrum with a power-law continuum and a soft excess during each NICER epoch. These emission sources demonstrate correlated flux variability with a lag consistent with zero days. We find that the power-law emission is consistent with a compact X-ray corona, and that the soft excess can be explained by reflected coronal emission from the inner accretion disk. We test the relationship between changes in the flux of the X-ray corona and the UVW2 continuum, finding strong correlation and a negative X-ray lag of less than 1 day. This is consistent with a scenario in which the X-ray corona drives the UVW2 light curve through thermal reprocessing.